Pengaruh Work Life Balance dan Stres Kerja Terhadap Kinerja Karyawan di CV Berkah Sarana Anugerah - Alfa Tianisa; Bakhtiar, Bakhtiar; Zulkifli Siregar (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of work life balance and job stress on employee performance at CV Berkah Sarana Anugerah in Medan. The research background is based on the phenomenon of long working hours, psychological pressure, and imbalance between work and personal life, which potentially reduce productivity. The research method employs a quantitative approach with the population consisting of all employees of CV Berkah Sarana Anugerah. Data collection was conducted through questionnaires developed based on indicators of work life balance, job stress, and employee performance. Data analysis utilized a structural model (Structural Equation Modeling) with evaluation of both the outer model and inner model. The findings reveal that work life balance has a positive and significant effect on employee performance, while job stress has a significant negative effect. Simultaneously, work life balance and job stress jointly influence employee performance. These results highlight the importance of organizational policies that support work life balance and effective stress management to ensure sustainable employee productivity and well-being.